การพัฒนาเชาวน์สังคมของนักเรียนวัยรุ่นโดยการปรึกษากลุ่มแบบบูรณาการ - เล็บขาว, ดุษฎี; กุลนภาดล, เพ็ญนภา; เกิดพิทักษ์, ผ่องพรรณ (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อศึกษาและพัฒนาเชาวน์สังคมของนักเรียนวัยรุ่นที่มีอายุระหว่าง 13-15 ปี ในโรงเรียนมัธยมศึกษาภาคตะวันออกเฉียงเหนือ กลุ่มตัวอย่างถูกแบ่งออกเป็น 2 กลุ่ม กลุ่มที่ 1 เพื่อศึกษาเชาวน์สังคมของนักเรียนวัยรุ่น จำนวน 1,031 คน คัดเลือกโดยการสุ่มแบบหลายขั้นตอน กลุ่มที่ 2 เพื่อพัฒนาเชาวน์สังคม คัดเลือกนักเรียนที่มีค่าเฉลี่ยคะแนนเชาวน์สังคมตั้งแต่เปอร์เซนไทล์ที่ 50 ลงมา จำนวน 20 คนและสุ่มอย่างง่ายเข้ากลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 10 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบวัดเชาวน์สังคมและรูปแบบการปรึกษากลุ่มแบบบูรณาการที่ผู้วิจัยพัฒนาขึ้น สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ การวิเคราะห์องค์ประกอบเชิงยืนยันและการวิเคราะห์ความแปรปรวนแบบพหุคูณชนิดวัดซ้ำ ผลการวิจัยสรุปได้ดังนี้ 1) เชาวน์สังคมนักเรียนวัยรุ่นโดยรวมอยู่ในระดับปานกลาง โดยองค์ประกอบด้านความร่วมรู้สึกอย่างแท้จริง ด้านการเอื้ออำนวยในสังคมอยู่ในระดับมาก ด้านการตระหนักรู้สถานการณ์ ด้านการแสดงตน ด้านการนำเสนอตนเองอยู่ในระดับปานกลาง 2) รูปแบบการปรึกษากลุ่มแบบบูรณาการเพื่อพัฒนาเชาวน์สังคมของนักเรียนวัยรุ่น 3) เชาวน์สังคมนักเรียนวัยรุ่นที่ได้รับการปรึกษากลุ่มแบบบูรณาการมีค่าเฉลี่ยคะแนนเชาวน์สังคมเพิ่มขึ้นกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 4) เชาวน์สังคมนักเรียนวัยรุ่นที่ได้รับการปรึกษากลุ่มแบบบูรณาการมีค่าเฉลี่ยคะแนนเชาวน์สังคมระยะหลังการทดลองและหลังการติดตามผลเพิ่มขึ้นกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The Development Of Adolescent Students’ Social Intelligence Through Integrative Group Counselling Model The purposes of this study were to study of adolescent students ‘s social intelligence and develop the integrative group counselling model for enhancement of social intelligence. The samples of this study were divided into 2 groups. The frst group of social intelligence study consist of 1,031 adolescent students. Those were selected by multi-stage sampling from population. The second group of the study was 20 adolescent students whose social intelligence score lower than 50th percentile and volunteered to attend the experiment. They were randomly assigned into two groups, classifed as an experiment group and control group. Each group consisted of 10 older persons. The research instruments were 1) a social intelligence scale 2) the integrative group counseling model. The research results were as follows 1) The total mean score and each dimension score of social intelligence: empathic accuracy and social facility were high, while the mean score of situation awareness, presence and self-presentation were medium. 2) The integrative group counselling model for the enhance of social intelligence was developed from the concepts and techniques of group counseling theories. 3) The social intelligence of experimental group after participating in the integrative group counselling model and after the follow-up were statistic signifcantly higher than before the experiment at .05 level. 4) The integrative group counselling model were effective in statistic signifcantly enhancing the social intelligence of adolescent students participated in the model at .05 level. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">